PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT.PUSKOPKAR RIAU PEKANBARU - Sari, Desria; ', Nuryanti; ', Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted at PT. Puskopkar Riau Pekanbaru, with the aim to determine the effect of Job Satisfaction and Organizational Commitment eithersimultaneously or partially on Employee Performance in PT. Puskopkar RiauPekanbaru. This study is a correlational study to examine the relationship between variables. The sample in this study is an employee of PT. Puskopkar Riau Pekanbaru as many as 58 people, and the data of this research is primary data derived from the questionnaire. Methods of collecting quantitative data using descriptive methods, and analysis of data using multiple regression analysis with the help of the SPSS (Statistical Package for Social Science) version 17. As an independent variable in this study is Job Satisfaction and Organizational Commitment and the dependent variable was Employee Performance. Based on the results of the F test is known that Job Satisfaction and Organizational Commitment simultaneously significant effect on employee performance. While based on the results of the t test is known that Job Satisfaction and Organizational Commitment partially significant effect on the performance of employees at PT. Puskopkar Riau Pekanbaru. Based on the test results obtained by the value of the coefficient of determination R Sguare in research, then this value will be changed to the shape percent. This means that the percentage contribution of the effect of variable Job Satisfaction and Organizational Commitment on Employee Performance in PT. Pekanbaru Riau Puskopkar 60.6%, while the remaining 39.4% influenced by variables not examined in this study.Keywords: Performance, Job Satisfaction and Organizational Commitment